2021
DOI: 10.14202/vetworld.2021.3156-3163
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of semen collection technique using electroejaculator and semen cryopreservation of Javan leopard (Panthera pardus melas Cuvier, 1809)

Abstract: Background and Aim: The Javan leopard (Panthera pardus melas Cuvier, 1809) is a subspecies of Panthera pardus spp., spread across the African and Asian regions. Information on reproductive aspects is crucial for wild animals, including the Javan leopard. In this study, we aimed to develop electroejaculator (EE) techniques and evaluate cryopreservation success in Javan leopard semen. Materials and Methods: The semen of four adult Javan leopards was collected once a week using EE. Placement of the EE probe in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The increased prevalence of coiled tails has been linked with various nongenetic etiology (Chenoweth 2005). The same incidence has been reported in wild felids such as clouded leopard (Neofelis nebulosa) (Tipkantha et al 2017), Javan leopard (Panthera pardus melas) (Mulia et al 2021), and mountain lion (Puma concolor) (Huffmeyer et al 2022).…”
Section: Discussionmentioning
confidence: 73%
“…The increased prevalence of coiled tails has been linked with various nongenetic etiology (Chenoweth 2005). The same incidence has been reported in wild felids such as clouded leopard (Neofelis nebulosa) (Tipkantha et al 2017), Javan leopard (Panthera pardus melas) (Mulia et al 2021), and mountain lion (Puma concolor) (Huffmeyer et al 2022).…”
Section: Discussionmentioning
confidence: 73%
“…This study's males have penile spines comparable to those reported by Silva et al (2019a) in jaguars. In addition, they had traits with the penile spines of other species from the same genus, including the Javan leopard P. pardus melas (Mulia et al, 2021), the Arabian leopard P. pardus nimr (Baqir et al, 2015), and the African lion P. leo (Schepper, 2016), but they were less numerous than other neotropical cat species of the genus Leopardus (Araujo et al, 2013;Machado et al, 2020;Morais et al, 2002). Araujo et al (2018) established in jaguars the pharmacological semen collection by combining medetomidine and ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Research on other wildlife animals also showed varied results. For example, in the Sunda clouded leopards, it was only 13.60% and 11.60% [ 47 ], 47.05% for Javan leopard [ 48 ], whereas in the rhino, it reached 91.40% [ 49 ].…”
Section: Discussionmentioning
confidence: 99%